Genealogy as critique : Foucault and the problems of modernity - Koopman, Colin (American philosophy., 2013)
Viewing Foucault in the light of work by Continental and American philosophers, most notably Nietzsche, Habermas, Deleuze, Richard Rorty, Bernard Williams, and Ian Hacking, this book shows that philosophical genealogy involves not only the critique of modernity but also its transformation. The author engages genealogy as a philosophical tradition and a method for understanding the complex histories of our present social and cultural conditions. He explains how our understanding of Foucault can benefit from productive dialogue with philosophical allies to push Foucaultian genealogy a step further and elaborate a means of addressing our most intractable contemporary problems.